The Role of Parents in the Use of Social Media in Early Childhood - Lailya Ika Ardiya; Ariningtyas Dwi R; Alfin Arina; Virginia Salsa Billa A.P.; Nur Farida R. (Proceedings of The ICECRS, 2020)
The digital era is information technology that can be accessed by anyone, anywhere and under any conditions, so that it can have a positive and negative impact on the responsibilities of parents to children. This study aims to determine the role of parents in the use of social media in early childhood. This research is a library research whose main source is library data. All library data is analyzed by using data analysis techniques with comparative descriptive techniques and critical analysis. Based on this research, parents are responsible for being more selective in caring for, caring for, educating, and protecting children in today's digital era. They are also required to understand technology and information systems.